Customer learning for value creation - Bailey, James Andrew (2014)
In value creating contexts, customers often have to be clear about the roles they are required to perform (Kleinaltenkamp et al., 2012; Bitner et al., 1997), and may be required to develop their knowledge and skills in order to participate (Hibbert et al., 2012). This typically necessitates the ability to use and integrate resources in exchange encounters containing social and economic actors (Kleinaltenkamp et al., 2012; Hibbert et al., 2012; Arnould et al., 2006; Sheth and Uslay, 2007) to co-create value for each other (Vargo and Lusch, 2008; Payne et al., 2008). This research adds to the burgeoning literature on customer resource integration that calls for more insights into the roles of customers in creating their own value (Hibbert et al., 2012; Kleinaltenkamp et al., 2012; Arnould et al., 2006). This can help firms to develop an appreciation of the customer value process and design co-creation activities that can support their customers’ capability to create value (Vargo, 2007; Vargo and Lusch, 2004; 2008; Sheth and Uslay, 2007; Prahalad and Ramaswamy, 2004; Payne et al., 2008; Frow et al., 2010).